Estrategias de aprendizaje y comprensión lectora en alumnos de quinto año de secundaria de una institución educativa del Callao - Barturén Silva, Matilde Luzmila (2012)
This is a descriptive-correlational research that aims to establish the relationship between learning strategies and reading comprehension in high school students in fifth of an educational institution of Callao. The sample was comprised of a total of 67 students. We used the Learning Strategies Scale ACRA (Roman & Gallego, 1994) and reading comprehension test (Tapia, 1982). The results show that there is significant correlation between low dimensions: strategies and information acquisition strategies of encoding information with reading comprehension. While between dimensions: strategies and information retrieval strategies and information support reading comprehension there is a low non significant.